SPECIFICITY OF ECOLOGICAL DISCOURSE IN THE XXI CENTURY - Skyba, Ivan (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. Awareness of the link between the environmental state and the accumulation of harmful effects ofhuman activities has led to the formation of certain social requirements for the political leadership of different countries to take urgent measures to protect the environment Research methods are a socio-philosophical study of the specifics of ecological discourse in the XXI c. The aim and tasks are sociocultural, cultural-historical, systemic, and comparative methodological approaches in their dialectical unity. Research results. Considering that ecological discourse can be viewed from two perspectives as a discourse reducedto issues of ecology as a science andas a discourse of the environment of man, the author explores ecological discourse in the broad sense of the word as an ecology of the mind, cognition, action, communication, creativity and more. This perspective gives ecological discourse an anthropological dimension, and the methodological foundations of new humanitarian (philosophical, sociological, psychological, pedagogical, educational, etc.) paradigms, including strategies of ecological thinking and environmental ethics, show the importance ofthe interdisciplinary synthesis of the knowledge at the level of discourse Discussion. From the perspectiveof functional and stylistic differentiation, the following types of ecological discourse are distinguished: scientific, media, religious-preaching, artistic. Conclusions. Along withthe formation of ecological discourse, there is the reverse side of the actualization of "ecological". Actualizationof the ecological is evidence of its scarcity. The solution to the ecological problem is both in the anthropological and socio-cultural dimensions.